Level of serum soluble Tim-3 expression in early-phase acute pancreatitis - Min Lin,; Jin Huang,; Jian Huang,; Sheng-lan Liu,; Wei-Chang Chen, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: T-cell immunoglobulin and mucin domain 3 (Tim-3) assumedly play a crucial immunomodulatory role in inflammatory response. Data on the potential role of soluble Tim-3 (sTim-3) in acute pancreatitis (AP) are scarce. We conducted a prospective clinical study to characterize its role in the early-phase AP. Methods: In total, 44 patients with AP (16 mild and 28 none-mild) who presented within 24 hours on admission and 20 healthy volunteers (NC) were included in our study. Serum interleukin (IL)-6, IL-10, tumor necrosis factor (TNF)-α, and sTim-3 levels were detected using enzyme-linked immunosorbent assay (ELISA). Results: Levels of the pro-inflammatory cytokines IL-6 and TNF-α and the anti-inflammatory cytokine IL-10 in the none-mild and mild groups were significantly elevated compared with those of the NC group. The sTim-3 levels of the none-mild and mild group were significantly increased compared with the NC. The sTim-3 level positively correlated with the IL-6 and TNF-α but showed no obvious correlations with the IL-10 level. The sTim-3 level positively correlated with the APACHE II score. Conclusion: The results indicate that sTim-3 participates in the early progression of AP by positively regulating the pro-inflammatory cytokines and that the measurement of serum sTim-3 is an early marker for predicting AP. Cite this article as: Lin M, Huang J, Huang J, Liu SI, Chen WC. Level of serum soluble Tim-3 expression in early-phase acute pancreatitis. Turk J Gastroenterol 2019; 30(2): 188-91.